2016
DOI: 10.1038/srep39031
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced positive selection maintains the functional divergence of duplicated DIHYDROKAEMPFEROL 4-REDUCTASE genes

Abstract: Gene duplication could be beneficial by functional division but might increase the risk of genetic load. The dynamics of duplicated paralogs number could involve recombination, positive selection, and functional divergence. Duplication of DIHYDROFLAVONOL 4-REDUCTASE (DFR) has been reported in several organisms and may have been retained by escape from adaptive conflict (EAC). In this study, we screened the angiosperm DFR gene focusing on a diversified genus Scutellaria to investigate how these duplicated genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
(109 reference statements)
2
4
0
Order By: Relevance
“…8 ) and was lower in Shepody, the control. DFRa expression was greater than DFRb expression in RedR3 but less than that in PurpleR2, consistent with the differences in cyanidin and delphinidin content between these varieties [ 40 ]: at the higher DFRa-type transcript spliceosomes content, cyanidin 3-O-galactoside, pelargonin, and pelargonidin 3-O-glucoside accumulated, producing the red color [ 41 ], and at the higher DFRb-type content, petunidin 3-O-glucoside, malvidin 3-O-glucoside, delphinidin 3-O-glucoside, and cyanidin 3-O-glucoside accumulated, producing the purple color [ 42 ]. In tobacco, AN1 overexpression caused anthocyanin accumulation, leading to purple leaves.…”
Section: Discussionsupporting
confidence: 64%
“…8 ) and was lower in Shepody, the control. DFRa expression was greater than DFRb expression in RedR3 but less than that in PurpleR2, consistent with the differences in cyanidin and delphinidin content between these varieties [ 40 ]: at the higher DFRa-type transcript spliceosomes content, cyanidin 3-O-galactoside, pelargonin, and pelargonidin 3-O-glucoside accumulated, producing the red color [ 41 ], and at the higher DFRb-type content, petunidin 3-O-glucoside, malvidin 3-O-glucoside, delphinidin 3-O-glucoside, and cyanidin 3-O-glucoside accumulated, producing the purple color [ 42 ]. In tobacco, AN1 overexpression caused anthocyanin accumulation, leading to purple leaves.…”
Section: Discussionsupporting
confidence: 64%
“…Mutations occurring at these sites are more likely to impact substrate binding a nities of the corresponding enzyme resulting in new speci c interactions (Reva et al, 2011). In this study, we found multiple, orthologous copies of both F3H and DFR to be present and here hypothesizes that duplication of these genes may have facilitated functional diversi cation of the ABP in Ruellia (Huang et al, 2016).…”
Section: Discussionsupporting
confidence: 49%
“…Prior research has demonstrated lower rates of non-synonymous mutations among genes upstream in the ABP pathway compared to downstream genes (Rausher et al, 1999), likely as a function of relaxed evolutionary constraint on downstream (vs. upstream) genes (Lu and Rausher, 2003) or high rates of positive selection on downstream genes, potentially playing a role in adaptive oral color evolution (Huang et al, 2016). This pattern is expected given that upstream enzymes function in a much broader set of biosynthetic pathways (e.g., lignin and other avonoids) than downstream enzymes, which are largely speci c to anthocyanin production ( Figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic-based analysis has shown that the growth form and flower color-related transcription factors (MYBs) are positively selected and are possibly related to the differentiation of flower color and speciation 12 . Divergent selection and functional subdivision of anthocyanin-biosynthetic genes have also been suggested to be responsible for the rapid evolution and diversification of Scutellaria species in the island of Taiwan 13 , 14 . In addition, biogeographic analyses have indicated a very recent divergence time, within 0.2 Mya, of these two species, and their divergence was suggested to be a consequence of a series of dispersal and vicariance events corresponding to climate shifts through the late Pleistocene 15 .…”
Section: Introductionmentioning
confidence: 99%